The other side of empire : just war in the Mediterranean and the rise of early modern Spain - Devereux, Andrew (Cornell University Press, 2020)
"The legal and moral arguments Spaniards developed to justify acts of war and conquest in Christian- and Muslim-ruled lands ringing the Mediterranean during the late fifteenth and early sixteenth centuries"--